Co-integration and Co-movement Between Asian Stock Price Index and Jakarta Composite Index - Stevanius, Stevanius; Sukamulja, Sukmawati (The Indonesian Capital Market Review, 2020)
The profit from international diversification to eliminate risks has caused investors to spread their capital to different international stock exchanges. The dynamic relations among stock exchanges indicate the presence of one or two-way relations among the stock exchanges. This happens because of the interdependence and integration that takes place among stock exchanges, such as interdependence among Asian markets. This research aims to analyze and discuss co-integration and co-movement between Asian stock price index and Indonesia. The research design used Vector Error Correction Model. The results of this research prove that in the short-term, there is a relationship between Kuala Lumpur Composite Index, Stock Exchange of Thailand Index, and Hang Seng Index against Jakarta Composite Index. In the results of co-integration test, there are co-integration and co-movement between the capital markets of Malaysia, Thailand, South Korea, Japan, Singapore, and Hong Kong with Indonesia capital market.